2005
DOI: 10.1073/pnas.0503463102
|View full text |Cite
|
Sign up to set email alerts
|

Gut mucosal T cell responses and gene expression correlate with protection against disease in long-term HIV-1-infected nonprogressors

Abstract: Limited information is available on the molecular mechanisms by which long-term HIV-1-infected nonprogressors suppress HIV-1 infection and maintain immune functions. The intestinal mucosal immune system is an early target for HIV-1 infection and severe CD4 ؉ T cell depletion. We evaluated mucosal T lymphocyte subsets, virus-specific cellular responses, gene expression profiles, and viral loads in intestinal mucosal biopsies of long-term nonprogressor (LTNP) patients as compared to chronically HIV-1-infected pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
127
3
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(142 citation statements)
references
References 23 publications
11
127
3
1
Order By: Relevance
“…In a smaller expression profiling study of GALT tissue, long-term nonprogressors had higher expression levels of many immune response genes, although the levels of expression of these genes were even greater in the noncontrollers. 19 It is possible that the controllers in our study have higher expression levels of immune response genes relative to HIV-negative healthy persons, but the levels are still relatively low with respect to the noncontrollers. Finally, it will be of interest to characterize the same set of parameters in HAART-suppressed patients who have undetectable viral loads as a result of drugmediated viral suppression as opposed to natural resistance.…”
Section: Cellular/molecular Signatures Of Hiv Progression E29mentioning
confidence: 79%
See 2 more Smart Citations
“…In a smaller expression profiling study of GALT tissue, long-term nonprogressors had higher expression levels of many immune response genes, although the levels of expression of these genes were even greater in the noncontrollers. 19 It is possible that the controllers in our study have higher expression levels of immune response genes relative to HIV-negative healthy persons, but the levels are still relatively low with respect to the noncontrollers. Finally, it will be of interest to characterize the same set of parameters in HAART-suppressed patients who have undetectable viral loads as a result of drugmediated viral suppression as opposed to natural resistance.…”
Section: Cellular/molecular Signatures Of Hiv Progression E29mentioning
confidence: 79%
“…6,19,25 Our analysis has validated some parameters of such activation that are concordant between the peripheral blood and rectosigmoid biopsy tissue. Using several forms of analysis, we have also For personal use only.…”
Section: Cellular/molecular Signatures Of Hiv Progression E29mentioning
confidence: 98%
See 1 more Smart Citation
“…The persistence of HIV reservoirs in the gut-associated lymphoid tissue (GALT) has been well documented, and detectable levels of HIV replication (RNA, DNA, and p24 protein) have been reported in tissue biopsy specimens from the upper and lower intestinal tracts (3)(4)(5). Studies have shown that ART-naive or treated subjects with HIV show decreased intestinal tissue expression of genes involved in mucosal repair and regeneration, while expression of genes regulating inflammation and immune activation is increased (2,(5)(6)(7). In addition, the expression of genes involved in intestinal epithelial integrity and barrier function, such as tight junctional proteins, as well as in nutrient and xenobiotic absorptive and digestive functions, such as drug-metabolizing enzymes, is also decreased in HIV-infected subjects compared to HIV-negative healthy volunteers (6).…”
mentioning
confidence: 99%
“…Studies have shown that ART-naive or treated subjects with HIV show decreased intestinal tissue expression of genes involved in mucosal repair and regeneration, while expression of genes regulating inflammation and immune activation is increased (2,(5)(6)(7). In addition, the expression of genes involved in intestinal epithelial integrity and barrier function, such as tight junctional proteins, as well as in nutrient and xenobiotic absorptive and digestive functions, such as drug-metabolizing enzymes, is also decreased in HIV-infected subjects compared to HIV-negative healthy volunteers (6). Collectively, these data suggest that HIV infection leads to the disruption of the integrity of the intestinal epithelial barrier and alteration in nutrient and drug absorption.…”
mentioning
confidence: 99%